A Flexible Inverse Lomax Weibull-Weibull Model for Survival and Reliability Data - Falgore, Jamilu Yunusa; Abubakar, Yahaya; Doguwa, Sani Ibrahim; Mohammed, Aminu Suleiman; Imam, Abdussamad Tanko (UUM Press, 2025)
In this paper, an extension of the Weibull distribution using Inverse Lomax Weibull-G (ILWG) called Inverse Lomax Weibull-Weibull Distribution (ILWWD) was introduced. The statistical properties of the ILWWD were also derived. This includes the moment, moment generating function, quantile function, and distributions of order statistics. The parameters of the ILWWD were estimated using the maximum likelihood estimates (MLE) method. Simulation studies were presented for three distinct cases. Survival regression was also presented. Goodness-of-fit statistics were employed to assess the effectiveness of the ILWWD and Log-ILWWD. This indicated that the proposed distribution is superior in fitting leukemia data. Lastly, the flexibility of the ILWWD was demonstrated using a real-life dataset. These suggest that the proposed distribution is superior in fitting the datasets presented in this study